Penegakan Hukum terhadap Tindak Pidana Penadahan Kendaraan Bermotor di Kota Kupang - Imenuel Lakat; Deddy R. Ch Manafe; Adrianus Djara Dima (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The crime of stealing a two-wheeled motor vehicle is one of the criminal offenses that is quite troubling in society in various regions of Indonesia and is ranked high compared to other cases. Motor vehicle theft is a simple crime that is very wrong when faced with the fact that today's perpetrators are professional and organized, the perpetrators of these crimes make motor vehicle theft a livelihood that generates a very large income. At this time, cases of motor vehicle seizures are rampant and even the impact is very detrimental to the community both in terms of economy and spirituality. This research is an empirical juridical research using interview guidelines for the Police, motor vehicle procurement perpetrators and the local community. The data collection technique uses interview guidelines and literature studies. The data used are primary data and secondary data. This research was conducted in Kupang City. Data processing and analysis techniques are carried out by editing, coding, classifying and tabulation data. The results of this study show that: (1) Law enforcement efforts carried out by the Police must be tightened using two ways of crime prevention, namely: Preventive Actions and Repressive Actions. (investigation and arrest of the perpetrator). (2) Factors that hinder the police in eradicating the crime of motor vehicle seizure are internal factors and external factors